Current understanding and neurobiology of epileptic encephalopathies - Auvin, Stéphane; Cilio, Maria Roberta; Vezzani, Annamaria (Neurobiology of disease, 2016)
Epileptic encephalopathies are a group of diseases in which epileptic activity itself contributes to severe cognitive and behavioral impairments above and beyond what might be expected from the underlying pathology alone. These impairments can worsen over time. This concept has been continually redefined since its introduction. A few syndromes are considered epileptic encephalopathies: early myoclonic encephalopathy and Ohtahara syndrome in the neonatal period, epilepsy of infancy with migrating focal seizures, West syndrome or infantile spasms, Dravet syndrome during infancy, Lennox-Gastaut syndrome, epileptic encephalopathy with continuous spikes-and-waves during sleep, and Landau-Kleffner syndrome during childhood. The inappropriate use of this term to refer to all severe epilepsy syndromes with intractable seizures and severe cognitive dysfunction has led to confusion regarding the concept of epileptic encephalopathy. Here, we review our current understanding of those epilepsy syndromes considered to be epileptic encephalopathies. Genetic studies have provided a better knowledge of neonatal and infantile epilepsy syndromes, while neuroimaging studies have shed light on the underlying causes of childhood-onset epileptic encephalopathies such as Lennox-Gastaut syndrome. Apart from infantile spasm models, we lack animal models to explain the neurobiological mechanisms at work in these conditions. Experimental studies suggest that neuroinflammation may be a common neurobiological pathway that contributes to seizure refractoriness and cognitive involvement in the developing brain.